2021
DOI: 10.47577/tssj.v26i1.5315
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the performance of the companies in Constanta County which operate in the real estate transactions field in the context of sustainable development

Abstract: As time went on, Constanta County has become one of the emerging poles of residential development in Romania, primarily due to its excellent positioning as an economic hub driven by international trade, doubled by a tourism potential with a high degree of long-term growth. In this context, performance measurement remains a constant concern of the entire economic sector that can ensure the progress of an entity. The purpose of this paper is to carry out a dynamic analysis over an 11-year period of the profit ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Another study carried out on companies from G7 member countries reflected that there is a positive link between the transparency of ESG score results and the financial performance of companies measured by ROA and ROC (Almeyda & Darmansyah, 2019). However, the results are not consistent in one direction (Biktimirov & Afego, 2022), ESG disclosure has been shown to have a negative influence on the value of companies in the energy sector and does not exert any influence on the value of companies in the medical field (Aivaz, 2021;Constantinescu, 2021). In general, however, several studies have identified a positive relationship between ESG disclosure and the company's financial performance (Alareeni & Hamdan, 2020).…”
Section: Literature Reviewmentioning
confidence: 93%
“…Another study carried out on companies from G7 member countries reflected that there is a positive link between the transparency of ESG score results and the financial performance of companies measured by ROA and ROC (Almeyda & Darmansyah, 2019). However, the results are not consistent in one direction (Biktimirov & Afego, 2022), ESG disclosure has been shown to have a negative influence on the value of companies in the energy sector and does not exert any influence on the value of companies in the medical field (Aivaz, 2021;Constantinescu, 2021). In general, however, several studies have identified a positive relationship between ESG disclosure and the company's financial performance (Alareeni & Hamdan, 2020).…”
Section: Literature Reviewmentioning
confidence: 93%
“…The two cities are the capitals of the two countries; they were chosen as examples of large capitals of post-communist countries. They were also the case studies from a 2012 study (Ianoş et al, 2012), which revealed some similarities with respect to their urban dynamics, especially with respect to land use conflicts due to the socialist interventions in the city center and post-communist developments in the fringes, aimed mostly for profit (Aivaz, 2021;Stan, 2022b). The study, published close to the midpoint of the period we analyzed, emphasizes a stronger implementation of environmental policies in Romania after the accession to the European Union.…”
Section: Methodsmentioning
confidence: 99%
“…In the generic sense, the predilection for creating a sustainable material base seems to confirm the prospects of continuity and profitability in the case of the companies which offer direct or indirect services to other entities, such as those in passenger transport. Although the number of companies operating in this economic subcategory is not very large at the level of Constanța County, it still includes a number of strong players on the local economic scene, being representative for a number of companies active in promoting innovation and environmental care (Aivaz and Avram, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%